Native Plant Growth-Promoting Rhizobacteria Containing ACC Deaminase Promote Plant Growth and Alleviate Salinity and Heat Stress in Maize (Zea mays L.) Plants in Saudi Arabia - Madeha A. Alonazi; Hend A. Alwathnani; Fahad N. I. AL-Barakah; Fahad Alotaibi (Plants)
Halotolerant, plant growth-promoting rhizobacteria (PGPR) are known to alleviate plant growth under abiotic stresses, especially those isolated from saline arid soils. In this study, 66 bacterial isolates, obtained from various habitats in Saudi Arabia, were characterized for their plant growth-promoting (PGP) traits, and screened for heat and salt stress resilience. Finally, selected halotolerant PGPR strains were assessed for their potential to improve maize (Zea mays L.) growth under salinity stress using in vitro assays. Our results indicated that many isolates possessed key PGP traits such ACC deaminase, N-fixation, and phytohormone production. Additionally, several isolates were able to tolerate high temperatures, and 20 bacterial isolates were classified as halotolerant. Furthermore, among the isolates, Pseudomonas soyae (R600), Bacillus haynesii (SFO145), Salinicola halophilus (SFO075), and Staphylococcus petrasii (SFO132) significantly enhanced various maize growth parameters under salt stress conditions when compared to uninoculated plants. These halotolerant PGPR are good candidates to be explored as bioinoculants for sustainable agriculture under saline arid soil conditions.